Microtitre plate measurement of platelet response to hypotonic stress. Issue 12 (December 1989) - Farrugia, A; Hughes, C; Douglas, S; Neal, M; James, J
Abstract : The conventional method of assessing the platelet response to hypotonic stress (HSR) was adapted to allow microtitre plate technology to be used. After water is added to a platelet suspension two sequential readings are taken at 414 nM on a vertical microplate reader. The difference between the second (three minutes) and the first (one minute) was defined as the HSR. This method allowed the relation between platelet concentrate pH and viability to be confirmed, and an HSR value for use in quality control was established. The method correlated well with the conventional technique and permitted measurement of undiluted samples as well as of products with a high free haemoglobin concentration.